IQGAP1 Regulates Adult Neural Progenitors In Vivo and Vascular Endothelial Growth Factor-Triggered Neural Progenitor Migration In Vitro - Balenci, Laurent (J Neurosci, 2007)
In the germinative zone of the adult rodent brain, neural progenitors migrate into niches delimited by astrocyte processes and differentiate into neuronal precursors. In the present study, we report a modulating role for the scaffolding protein IQGAP1 in neural progenitor migration. We have identified IQGAP1 as a new marker of amplifying neural progenitor and neuronal precursor cells of the subventricular zone (SVZ) and the rostral migratory stream (RMS) in the adult mouse brain. To determine functions for IQGAP1 in neural progenitors, we compared the properties of neural progenitor cells from wild-type and Iqgap1-null mutant mice in vivo and in vitro. The in vivo studies reveal a delay in the transition of de novo neural progenitors into neuronal precursor cells in Iqgap1-null mice. In vitro, we demonstrated that IQGAP1 acts as a downstream effector in the vascular endothelial growth factor (VEGF)-dependent migratory response of neural progenitors that also impacts on their neuronal differentiation. The Rho-family GTPases cdc42/Rac1 and Lis1 are major partners of IQGAP1 in this migratory process. Finally, astrocytes of the neurogenic SVZ and RMS are shown to express VEGF. We propose that VEGF synthesized by astrocytes could be involved in the guidance of neural progenitors to neurogenic niches and that IQGAP1 is an effector of the VEGF-dependent migratory signal.